Regional Cerebral Disease Progression in Friedreich's Ataxia: A Longitudinal Diffusion Tensor Imaging Study. Issue 2 (14th July 2015) - Mascalchi, Mario; Toschi, Nicola; Giannelli, Marco; Ginestroni, Andrea; Della Nave, Riccardo; Tessa, Carlo; Piacentini, Silvia; Dotti, Maria Teresa; Aiello, Marco; Nicolai, Emanuele; Soricelli, Andrea; Salvi, Fabrizio; et al.
ABSTRACT: BACKGROUND AND PURPOSE: Imaging biomarkers of disease progression are desirable in inherited ataxias. MRI has demonstrated brain damage in Friedreich ataxia (FRDA) in form of regional atrophy of the medulla, peridentate cerebellar white matter (WM) and superior cerebellar peduncles (visible in T1‐weighted images) and of change of microstructural characteristics of WM tracts of the brainstem, cerebellar peduncles, cerebellum, and supratentorial structures (visible through diffusion‐weighted imaging). We explored the potential of brain MR morphometry and diffusion tensor imaging (DTI) to track the progression of neurodegeneration in FRDA. METHODS: Eight patients (5F, 3M; age 13.4‐41.2 years) and 8 healthy controls (2F, 6M; age 26.2‐48.3 years) underwent 2 MRI examinations (mean 3.9 and 4.1 years apart, respectively) on the same 1.5T scanner. The protocol included 3D T1‐weighted images and axial diffusion‐weighted images (b‐value 1, 000 s/mm 2 ) for calculating maps of fractional anisotropy, mean, axial and radial diffusivity, and mode of anisotropy. Tensor‐based morphometry was used to investigate regional volume changes and tract‐based spatial statistics was used to investigate microstructural changes in WM tracts. RESULTS: Longitudinal analyses showed no differences in regional volume changes but a significant difference in axial diffusivity changes in cerebral and corpus callosum WM of patients as compared to controls (mean longitudinal rate of change for axial diffusivity: −.02 × 10 ‐3 mm 2 /s/year in patients vs. .01 × 10 ‐3 mm 2 /s/year in controls). No correlation with number of triplets, disease duration, and worsening of the clinical deficit was observed. CONCLUSION: DTI can track brain microstructural changes in FRDA and can be considered a potential biomarker of disease progression.